Performance of generator negative-sequence protection during single-phase fault - Ali Mohd. Jobran, Junaidah (2012)
Negative-sequence current is a component that resulted from unbalance conditions that occur in the system. Theoretically, problems caused by the negativesequence current are rare and can be ignored, but in reality the presence of negative sequence current which exceeds the permitted level will affect the performance of the generator. Therefore, some utility companies tend to adopt more passive method by tripping and separating the generator from the system if negative-sequence current is higher than the predefined level. However, tripping of major generation facilities may create social, security and economic problem. In order to protect the generator from negative-sequence current, there are many methods can be used as the negativesequence protection. One of the methods is using negative-sequence impedance directional element. In this project, several types of unbalanced conditions are tested on the parallel system, which have four main parts to be completed namely threephase parallel line system, breaker control, fault control and negative-sequence protection system. The design circuit is constructed and simulated using PSCAD/EMTDC software, to check the comparison between the generator with negative-sequence protection and generator without negative-sequence protection. The data are analyzed based on the rms value of the generator, to evaluate the generator’s performance during unbalanced conditions. From the result, it shown that the performance of the generator with negative-sequence protection is stable with very small value of negative-sequence current compared to the generator without negative-sequence protection. In the end, new techniques are suggested as the alternatives to improve the performance of the generator.